Functional Dependency in Mexico: Measurement Issues and Policy Challenges - Villalobos-Dintrans, P (Kerman University of Medical Sciences, 2022)
Background: Different definitions have been used to measure functional dependency (FD) in Mexico. This study aims to explore if different definitions of FD lead to low consistency between the estimations of its prevalence. Accurate estimations of FD are useful to estimate the potential demand for long-term care (LTC) services in the country. Methods: A literature review including documents with estimations on the number or prevalence of dependents in Mexico with national representativeness between 2000 and 2019 was performed as well as estimations of different definitions of FD, using the National Study on Health and Aging in Mexico (ENASEM). Results: There is a lack of consensus on the definition of FD. Among the most frequently used terms to define FD are “disability” and “dependency.” The heterogeneity of definitions results in a wide range of estimations of the demand for LTC. Methodological choices can lead to important differences in FD prevalence estimations. Results from ENASEM 2001 show that FD prevalence could range from 13% to 35% in people 60+; sex prevalences also vary when using different ways to measure FD. Conclusion: Besides the highlighted issues in calculating FD in the population, Mexico should consider broadening the assessment of FD, including people with dementia and younger populations. Although the literature search is not systematic, it helps exemplifying the current issues when measuring FD in Mexico. A consensual definition of dependency is required to have a more accurate estimated demand for LTC. Having good data sources is not enough when dissimilar estimations of an indicator like dependency result from the same study. Wide heterogeneity in estimations of dependency could be an obstacle to inform public policies during the construction of a care system in Mexico. © 2022 The Author(s); Published by Kerman University of Medical Sciences.